2013
DOI: 10.3329/mh.v1i2.14088
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Bacteria in the Respiratory Tract of Apparently Healthy Quails

Abstract: A B S T R A C TThe study was undertaken for isolation, identification and in vitro antibiotic sensitivity assay of bacteria present in the respiratory tract of apparently healthy Japanese quails. A total of 50 samples comprised of tracheal swabs (n = 18), tracheal washings (n = 8), air sacs (n = 8), lungs (n = 8) and exudates of infraorbital sinuses (n = 8) were aseptically collected from 26 apparently healthy Japanese quails. The samples were inoculated onto a variety of media for isolation of bacteria. Ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…In this study, the isolates of E. coli were found to ferment the five basic sugars with the production of both acid and gas (Figure 4). Similar sugar fermentation test results were reported by several authors [21,22,25]. Results of sugar fermentation, motility and biochemical testsare summarizes in the Table (2).…”
Section: Identification Of E Colisupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, the isolates of E. coli were found to ferment the five basic sugars with the production of both acid and gas (Figure 4). Similar sugar fermentation test results were reported by several authors [21,22,25]. Results of sugar fermentation, motility and biochemical testsare summarizes in the Table (2).…”
Section: Identification Of E Colisupporting
confidence: 85%
“…Colony characteristics of E. coli observed in EMB and MC agar and found green metallic sheen colony in EMB agar and rose pink lactose fermented colony in MC agar (Figure 1). Similar Colonial feature were reported by [21,22]. In Gram's staining isolated bacteria were found Gram negative short rod in single or paired arranged (Figure 2) which was supported by several authors [21][22][23].…”
Section: Isolation Of E Colisupporting
confidence: 84%
See 1 more Smart Citation
“…Two studies reported the dissemination of MDR Salmonella in unconventional farming systems. Apparently healthy quails and pigeons were found to carry MDR Salmonella with resistance against amoxicillin (90%), ampicillin (80%), erythromycin (80%), tetracycline (60%), chloramphenicol (40%), kanamycin (40%), gentamicin (40%), nalidixic acid (40%), sulfamethoxazole (30%), and ciprofloxacin (20%) [ 32 , 39 ]. In LBM, broiler meat, poultry slaughterers’ hand, and poultry residual containers harbored MDR Salmonella with the highest resistance to imipenem (83.33%) [ 22 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of eight ABR bacterial species were reported in layer, broiler, backyard poultry, ducks, pigeons, and quails in nine different districts of Bangladesh (Table-1) [8,15,16,22,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. ABR Escherichia coli was identified in different types of birds from both conventional and unconventional farming systems in different areas of Bangladesh.…”
Section: Antibiotic-resistant Bacteria Reported In the Poultry Sectormentioning
confidence: 99%